Experts’ Opinion in Fabry Disease Management and the Unmet Medical Need: The Saudi Perspective - Alfadhel M; Al Sannaa N; Sunbul R; Al-Khawaja H; Askandarani S; Alanzi T; Elawad M; Fourtounas K (Dove Medical Press, 2024)
Majid Alfadhel,1- 3 Nouriya Al Sannaa,4 Rawda Sunbul,5 Huda Al-Khawaja,6 Sumayah Askandarani,7 Talal Alanzi,8 Mamoun Elawad,9 Konstantinos Fourtounas10 1Medical Genomics Research Department, King Abdullah International Medical Research Center, Ministry of National Guard Health Affairs (MNG-HA), Riyadh, Saudi Arabia; 2King Saud Bin Abdulaziz University or Health Sciences (KSAU-HS), Ministry of National Guard Health Affairs (MNG-HA), Riyadh, Saudi Arabia; 3Genetics and Precision Medicine Department (GPM), King Abdullah Specialized Children's Hospital (KASCH), King Abdulaziz Medical City, Ministry of National Guard Health Affairs (MNG-HA), Riyadh, Saudi Arabia; 4Johns Hopkins Aramco Healthcare, Dhahran, Kingdom of Saudia Arabia; 5Medical Genetic Unit, Pediatric Department, Qatif Central Hospital, Qatif, Saudia Arabia; 6Maternity and Children Hospital, Al Mubarraz, Al-Ahsa, Kingdom of Saudia Arabia; 7Multiorgan Transplant Center, King Fahad Specialist Hospital, Dammam, Eastern Province, Saudi Arabia; 8Division of Clinical Genetics and Metabolic, Department of Pediatrics, Prince Sultan Medical City, Riyadh, Saudi Arabia; 9Prince Sultan Military Medical City, Riyadh, Kingdom of Saudia Arabia; 10Prince Sultan Kidney Center, King Salman Armed Forces Hospital, Tabuk, Kingdom of Saudia ArabiaCorrespondence: Majid Alfadhel, Genetics and Precision Medicine Department, King Abdullah Specialized Children's Hospital (KASCH), King Abdulaziz Medical City(KAMC), Ministry of National Guard Health Affairs(MNG-HA), Riyadh, Saudi Arabia, 22490, 11426, Tel +966 11 805 3560, Fax +966 11 805 5555, Email dralfadhelm@gmail.comAbstract: Fabry disease (FD) is an X-linked lysosomal storage disorder caused by α-galactosidase A gene mutations. Its global incidence ranges from 1:40,000 to 1:170,000. This expert review evaluates the available guidelines, the status of diagnosed but untreated patients with FD, and the challenges in diagnosing and managing FD in the Kingdom of Saudi Arabia (KSA). An advisory board meeting (ABM) was conducted in two phases, with a survey that aimed to receive insights on the current unmet needs in the management of patients with FD in November 2022, and a second, offline meeting in February 2023. The goal of this ABM was to discuss current unmet needs in the management of Fabry patients in the Kingdom of Saudi Arabia. In the first ABM, experts opined on the best practices in the diagnosis, screening, and management of FD for healthcare professionals. These opinions on the management of FD relied on data from research and expert clinical judgments. In the second ABM, the same panel discussed different aspects of FD diagnosis, treatment, and management in the member countries of the Gulf Cooperation Council. The experts discussed the stigma associated with FD, patient awareness and knowledge, genetic screening, biomarkers, and home infusion therapy. They reviewed international guidelines and clinical criteria for enzyme replacement therapy (ERT). Furthermore, they also discussed the diagnosis of FD in men and women, the current guidelines followed for monitoring patients with FD, monitoring untreated patients with FD, Fabry Stabilization IndeX (FASTEX) as an assessment tool for the diagnosis of FD, FD management in KSA, challenges encountered while prescribing ERT in patients with FD, and the clinical criteria for starting ERT. The discussions led to the conclusion that currently, ERT is the only available therapy to manage FD and research should be focused on the early diagnosis and management of FD.Keywords: classical, enzyme replacement therapy, Fabry disease, late-onset, monitoring, phenotype